Pengembangan Kecerdasan Emosional Dan Spiritual Pada Siswa Program Pendidikan Tahfidz - Restu Banu Aji (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2024)
The purpose of this study was to determine the level of emotional and spiritual intelligence in Tahfidz Al-Qur'an. This type of research is descriptive qualitative with data collection techniques carried out by interview and observation. Based on the results of the study revealed that in general students of the Tahfidz program had good emotional intelligence. There are several steps taken to develop emotional intelligence including increasing self-awareness, self-regulation, fostering motivation, increasing empathy, fostering good relationships among fellow community members at school. Both students of the Qur'an's tahfidz program have good spiritual intelligence. The method of development is like always getting closer to Allah, often following social activities, open to change and trying to do the slightest good